Parallelization in a spatially explicit individual-based ecological model—1. Spatial data interpolation - Luh, Hang-Kwang; Abbott, Catherine A.; Berry, Michael W.; Comiskey, E.Jane; Dempsey, John C.; Gross, Louis J. (Computers & geosciences, 1997)
In this paper, we compare parallel implementations for spatial data interpolation on two parallel computers, MasPar MP-2 and CM-5, with the sequential implementations on a serial computer, SUN SPARCStation 20/61. Performance statistics indicate that: (1) parallel implementations can attain significant speed improvements over sequential implementations in a long-term simulation (above 100 time steps); (2) a data parallel algorithm using the local map method performs better than the partitioned map method on the MasPar MP-2, but there is no significant difference between them on the CM-5; and (3) for the particular problem of spatial data interpolation, the SIMD parallel computer (the MasPar MP-2 with 4096 processor elements) performs better than the MIMD parallel computer (the CM-5 with 32 parallel processing nodes).